PENGARUH BUNGA PASAR, KUPON DAN MATURITY TERHADAP HARGA OBLIGASI DI BURSA EFEK INDONESIA - Satria Wijaya, I Gusti Ngurah; Panji Sedana, Ida Bagus; Sri Artini, Luh Gede (Buletin Studi Ekonomi; VOL.20.NO.1.FEBRUARI 2015 (PP 1-82), 2016)
The Effect Of Market Interest, Coupon and Maturity To Bond Price In Indonesia Stock Exchange. Research on perceived bond is still limited compared to research on stocks in Indonesia. Bonds could be one type of asset is quite interesting, because it is able to provide fixed-income bonds for investors who do not like the risk and can be used as an alternative investment than shares. This research purposes to find the effect of market interest rates, interest rate coupon and maturing bonds against bond prices in Indonesia Stock Exchange. The population in research are all recorded corporate bonds be marketed on the Indonesia Stock Exchange (IDX) from 2009 to 2011 with sample size is as much as 115 bond. Research hypothesis testing used multiple linear regression analysis techniques. Based on the output of the analysis be discovered that the market interest rate is significantly negative effect on bond prices, the coupon rate is significantly positive effect on bond prices, and the maturities are significantly negative effect on bond prices. Keywords: Market Rate, Coupon Rate, Term Maturity, Bond Prices.
Keywords: Market Rate, Coupon Rate, Term Maturity, Bond Prices.